HOTS IN EXERCISE OF ENGLISH TEXTBOOK AT SMPN 24 KOTA BENGKULU - Novia Eka Pangesti; Alamsyah Harahap; Erni Sukesi (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2026)
This research aimed at determining the  the distribution and the highest frequency of the Higher Order Thinking Skills (HOTS) based on the revised edition of Blooms Taxonomy in the exercises of English textbook entitled Buku Bahasa Inggris “Think Globally Act Locally” SMP/MTS Kelas IX (Kurikulum 2013) for 9th grade students that use at SMPN 24 Kota Bengkulu. The researcher used the descriptive qualitative method. The researcher used 106 exercises of the English textbook as the data sources and the checklist table for collecting and used the Miles and Huberman’s theory for analyzing the data to find the result of the study. The result showed that the Higher Order Thinking Skills (HOTS) gained differently among skills of HOT and the English Textbook has no gradation or uneven, the author did not emphasize the distribution HOTS according to the students' level of thinking in each exercise in each chapter of the English book Furthermore the highest frequency of HOTS in this study belongs to the C6 (Creating). Therefore, it is suggested that teacher should choose the exercises in English Textbook that appropriate for the students’ need and level. For the author of English Textbook, need to pay attention to the gradation of distribution for each cognitive level in order to produce English textbooks that are appropriate to the level of education and thinking level of students.